Learning Indonesian History Based on Multiculturalism to Strengthen National Integration - Sulistiyono, Singgih Tri; Amaruli, Rabith Jihan (Diponegoro University, 2022)
This article discusses the importance of learning Indonesian history based on multiculturalism to strengthen national integration. The post-Reformation era, which has opened the gate to broad democracy and regional autonomy on the one hand, has also opened the idea of national disintegration by several parties on the other side. This idea demonstrated by demands for secession in several regions in Indonesia, the idea of trans-national Islam, and horizontal conflicts. If this is not a concern, it will threaten the conception of the Negara Kesatuan Republik Indonesia (NKRI)/Unitary State of the Republic of Indonesia in the future. Through the conception of multiculturalism, this article discusses three main things, namely the concept of multiculturalism in Indonesia, the plurality of Indonesian society as a necessity, and initiating learning Indonesian history through intellectual training and current problem-based learning strategies.